2017
DOI: 10.1007/s10661-017-6009-0
|View full text |Cite
|
Sign up to set email alerts
|

Presence of pesticide residues on produce cultivated in Suriname

Abstract: Agricultural pesticides are widely used in Suriname, an upper middle-income Caribbean country located in South America. Suriname imported 1.8 million kg of agricultural pesticides in 2015. So far, however, national monitoring of pesticides in crops is absent. Reports from the Netherlands on imported Surinamese produce from 2010 to 2015 consistently showed that samples exceeded plant-specific pesticide maximum residue limits (MRLs) of the European Union (EU). Consumption of produce containing unsafe levels of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Agriculture is a developing sector in Suriname, which contributes approximately 9% to the Gross Domestic Product (GDP) and employs 17% of the population [ 45 , 46 ]. Screening data from the Dutch Food and Consumer Product Safety Authority (NVWA) from 2010 to 2015 consistently showed pesticide residues in crops imported from Suriname [ 47 ]. The Caribbean Consortium for Research in Environmental and Occupational Health (CCREOH) is examining the association of pesticide exposure to birth outcomes in 1000 mother/child dyads [ 48 ].…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Agriculture is a developing sector in Suriname, which contributes approximately 9% to the Gross Domestic Product (GDP) and employs 17% of the population [ 45 , 46 ]. Screening data from the Dutch Food and Consumer Product Safety Authority (NVWA) from 2010 to 2015 consistently showed pesticide residues in crops imported from Suriname [ 47 ]. The Caribbean Consortium for Research in Environmental and Occupational Health (CCREOH) is examining the association of pesticide exposure to birth outcomes in 1000 mother/child dyads [ 48 ].…”
Section: Case Studiesmentioning
confidence: 99%
“…CCREOH’s preliminary environmental assessment showed pesticide residues in Surinamese produce, including the insecticides endosulfan and lindane in the leafy vegetable Xanthosoma brasiliense (tannia). According to an interviewer-assisted dietary survey, which was administered to assess dietary exposure to pesticides in Surinamese women (including 696 pregnant women), women living in non-urban districts and less educated women were more likely to have a higher tannia intake rate compared to those living in urban districts and women who received higher levels of education [ 47 ]. This disparity in exposure to tannia illustrates how pesticide use can have inequitable consequences for food safety based on region and education level.…”
Section: Case Studiesmentioning
confidence: 99%
“…An assessment of Surinamese agricultural produce showed pesticide residues exceeding European Union maximum residue limits, including prohibited worldwide endosulfan and lindane in the leafy vegetable tannia, Xanthosoma brasiliense . 35 An interviewer-assisted NHANES-based dietary survey of 522 participants showed that 98.2% reported consumption of leafy vegetables. Tannia was the most frequently consumed (89.3%); 36.5% participants had high intake rates of tannia (≥36 g/day).…”
Section: Findings To Datementioning
confidence: 99%
“…Future research will focus on monitoring fungicide residues by ELISA tests. Leyva Morales et al [32], also identified fungicides as the group with the highest frequency of use in northwestern Mexico; Wahid et al [33] cite fungicides as the second pesticide group imported after herbicides in Suriname. Additionally, EFSA [34] reported in the 2015 annual report of pesticides in food, fungicides as the most frequent pesticides with concentrations equal to or greater than the LOQ found.…”
Section: Screened Samplesmentioning
confidence: 99%